2008
DOI: 10.1525/mp.2008.26.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Verbal and Visual Material in Highly Trained Musicians

Abstract: INTEREST IN STUDYING THE EFFECTS of extensive music training on nonmusical perceptual and cognitive abilities has grown in recent years. Here, we present evidence that formal music instruction is associated with superior verbal and visual memory. Participants included 15 highly trained pianists and 21 individuals with little or no formal music training. The groups were comparable in terms of age, gender distribution, and socioeconomic status. Musicians showed superior immediate and delayed recall of word lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 54 publications
10
146
6
1
Order By: Relevance
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 75%
“…Studies comparing nonmusicians with musicians who began training early in life have revealed a "signature" set of enhancements associated with musical experience (27,28). Relative to nonmusician peers, musicians tend to show enhanced speech-innoise perception (29)(30)(31)(32)(33)(34), verbal memory (30)(31)(32)(33)(35)(36)(37)(38), phonological skills (39)(40)(41)(42)(43)(44)(45), and reading (46-50), although not without exception (51,52). Music training has also been linked to enhancements in the encoding of sound throughout the auditory system.…”
mentioning
confidence: 99%
“…Better results in academic achievement and an influence on executive functions and short-term memory were found in individuals subjected to orchestral musical instrument training; the longer the training, the greater its effects on the monitored functions and academic achievement (Holochwost et al, 2017). Some current studies are based on comparing non-musicians with musicians who had formal music education at music schools and conservatories (Jakobson et al, 2008;Cohen et al, 2011).…”
Section: Types Of Musical Activities Used For Learningmentioning
confidence: 99%
“…The consistent pattern of higher verbal abilities and verbal memory in children enrolled in music lessons (Ho et al, 2003;Moreno et al, 2011) is also found in adult musicians (Brandler & Rammsayer, 2003;Brown, Martinez, & Parsons, 2006;Jakobson, Lewycky, Kilgour, & Stoesz, 2008). However, some have proposed that rather than strengths in verbal memory because of the similarity in structure between music and language, adult musicians should have stronger visual memory than non-musicians because of the way musical notation is presented (Jakobson, et al, 2008).…”
Section: Cognitive Differences Between Musicians and Non-musiciansmentioning
confidence: 68%
“…However, some have proposed that rather than strengths in verbal memory because of the similarity in structure between music and language, adult musicians should have stronger visual memory than non-musicians because of the way musical notation is presented (Jakobson, et al, 2008). At least two studies have examined verbal and/or visual memory (Brandler & Rammsayer, 2003;Jakobson et al, 2008), and both found that musicians showed significantly better recall in verbal memory compared to non-musicians. Only one of the two studies (Jakobson et al, 2008) examined visual memory in addition to verbal memory and found that adult musicians also had higher visual memory than non-musicians.…”
Section: Cognitive Differences Between Musicians and Non-musiciansmentioning
confidence: 99%